Tari Kontemporer Space Karya Mu’ammar Ghadafi Kota Pekanbaru Provinsi Riau - Nadia Rahmadani; Syefriani Syefriani (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
This thesis aims to find out the Space Contemporary Dance by Mu'ammar Ghadafi in Pekanbaru, Riau. This dance was created in 2020. It was first performed at the PASTAKOM (Contemporary Dance Market) event at the Pekanbaru Cultural Park. This research uses a descriptive method by using qualitative data. The data collection is taken by observation, interviews and documentation. In this study, the research subjects consisted of 5 people. They are 1 choreographer (Mu’ammar Ghadafi), 3 dancers (Muhammad Sukri, Izadri and Iqbal), and 1 musician (Sulaiman). It used Soedarsono's theory. Space Contemporary Dance has some elements in the movements such as igal, acrobatics, jumping, body writhing, hand and zapin fist movements. The music used is a digital musical instrument. The dramatic design in this dance is in the form of a single cone dramatic design because the stages of the flow in this dance are increasing towards the climax and slowly continuing to the decreasing stage. The dynamics in this dance are changes in level and tempo. The main theme is about the relationship between human social life and God of the universe. The clothes used in this dance only uses black shorts without top. This dance uses beautiful and bold make-up. It does not use props, only shawl accessories.